Effects of Group Process Program on Knowledge and Behaviors of Disease Control and Blood Pressure of Essential Hypertensive Patients in Hypertension Clinic At Wiang Pa Pao Hospital, Chiangrai Province - คำหล้า วัชรพงษ์ (Journal of Preventive Medicine Association of Thailand, 2018)
This experimental research aimed to study the effects of group process program on knowledge and behaviors of disease control and blood pressure of essential hypertensive patients. Sample consisted of 82 essential hypertensive patients who aged between 35 to 59 years old and treated at Hypertension Clinic, Wiang Pa Pao Hospital, Chiangrai Province. They were primary selected by purposive sampling into experimental and control group with inclusion criteria, each group composed of 41 patients. Research instruments were the programs of group process, questionnaires and sphygmonometer. The results of this study revealed that the mean score of knowledge, behaviors of disease control and blood pressure of the experimental group was met that after the 8 th week of program of group process were better than before start this program. The results revealed statistically significant as (p<0.001). The mean score of knowledge about the disease, behaviors of disease control and blood pressure between the experimental group and the control group after the 8th weeks of program of group process and the 12th weeks of follow-up were difference. The statistically significant was shown as (p<0.001). The mean score of knowledge, behaviors of disease control and blood pressure of the experimental group in the trial period of intervention were different. Long-term follow-up after intervention program were better than before start the experimental program, which showed statistically significant as (p<0.001). The results of this study indicated that the group process program helped essential hypertensive patients for more knowledge and better behaviors of disease control than past and lower blood pressure levels as well. This program can be extended to apply to the other group of patients with high blood pressure or other groups that were treated hypertension at primary or secondary care unit in Wiang Pa Pao district. We can apply this program to patients with other chronic non-communicable diseases.